2015
DOI: 10.1111/his.12474
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf‐1 expression is down‐regulated during the colorectal adenoma–carcinoma sequence and correlates with reduced microvessel density and VEGF expression

Abstract: This study is the first to show the roles of Dkk1 during the colorectal adenoma-carcinoma sequence, which may involve suppression of the tumorigenesis and angiogenesis of CRC. Dkk1 could therefore serve as a potential target for tumour therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
1
35
1
Order By: Relevance
“…This suggests that the WNT/␤-catenin-mediated metabolic reprogramming of cancer cells can directly affect vessel density in tumors. In fact, in other models, canonical WNT signaling has been strongly linked to tumor angiogenesis by directly regulating the expression of the proangiogenic growth factor (GF) vascular endothelial GF (56)(57)(58). Since blood vessels deliver nutrients and O 2 to tissues, it is hardly surprising that metabolism and angiogenesis should be coregulated by WNT signaling.…”
Section: Canonical Wnt Signaling and Cancer Cell Metabolismmentioning
confidence: 99%
“…This suggests that the WNT/␤-catenin-mediated metabolic reprogramming of cancer cells can directly affect vessel density in tumors. In fact, in other models, canonical WNT signaling has been strongly linked to tumor angiogenesis by directly regulating the expression of the proangiogenic growth factor (GF) vascular endothelial GF (56)(57)(58). Since blood vessels deliver nutrients and O 2 to tissues, it is hardly surprising that metabolism and angiogenesis should be coregulated by WNT signaling.…”
Section: Canonical Wnt Signaling and Cancer Cell Metabolismmentioning
confidence: 99%
“…DKK-1 is downregulated in a number of tumors, of which colon cancer is the most paradigmatic. We and others have reported reduced expression of DKK-1 in colon cancer [11,42] that in a proportion of cases is associated with promoter hypermethylation [20,43,44] . This was an unexpected finding because as a β-catenin/TCF target DKK-1 gene was predicted to be upregulated in a malignancy characterized by a constitutively hyperactivated Wnt/β-catenin pathway.…”
Section: Research Highlightmentioning
confidence: 66%
“…Supporting these data, analysis of DKK-1 expression in human colon tumors demonstrated an inverse correlation with tumor grade, presence of metastasis, and recurrence [45] . Moreover, downregulation of DKK-1 expression is concomitant with reduced epithelial-to-mesenchymal transition (EMT) phenotype [45] , and with reduced angiogenesis and VEGF expression [42] . The complex behavior of DKK-1 as a tumor suppressor or metastasis promoter may rely on the diverse and sometimes opposite actions of Wnt/β-catenin signaling in different tissues, together with other Wnt-independent effects that may add to the array of DKK-1 actions.…”
Section: Research Highlightmentioning
confidence: 99%
“…On the other hand, the expression pattern of Dkk-1, an inhibitor of Wnt/b-catenin pathway, by blocking Wnt signaling receptor complexes and contributing to colon cancer suppression, is remarkably downregulated in the colonic biopsies of colorectal cancer patients, and its downregulation is disclosed as a biomarker of chemoresistance and poor clinical outcome (25)(26)(27)(28)(29). Although the overall available data still have discrepancies, Dkk-1 has been found to not only act as an inhibitor of Wnt/ b-catenin signaling but also has additional b-catenin-independent tumor suppressor, antiangiogenesis, and antimetastasis actions in colorectal cancer disease (27,41). Likewise, CDNK-1A, a tumor suppressor gene encoding a potent cell-cycle inhibitory factor (CDKN1A, p21, or CIP1), is downregulated or even lost in most colorectal cancer cases (30), and some colorectal cancer patients have anti-CDKN1A autoantibodies in their colorectal tissues (31).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, CDNK-1A, a tumor suppressor gene encoding a potent cell-cycle inhibitory factor (CDKN1A, p21, or CIP1), is downregulated or even lost in most colorectal cancer cases (30), and some colorectal cancer patients have anti-CDKN1A autoantibodies in their colorectal tissues (31). On the basis of these facts, it is conceivable that targeting these crucial colorectal tumorigenesis pathways, through repression of Wnt/b-catenin activity and/or stimulation of Dkk-1 and CDNK-1A, may hold tremendous therapeutic potential in treating colorectal cancer and other cancers, and in enhancing the cytotoxic effects of chemotherapeutic agents (25,41). Interestingly, data of the current study are in agreement and showed that cotherapy with paricalcitol and 5-FU significantly interacted to repress the overexpressed Wnt and b-catenin, and upregulated the decreased Dkk-1 and CDNK-1A in the colorectal tissues of the chemically induced colorectal cancer model, suggesting a cooperative mechanism between the two drugs that, in part, might be behind their observed tumoricidal effect.…”
Section: Discussionmentioning
confidence: 99%